2007
DOI: 10.1016/j.bbr.2007.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Deletion of Lsamp Causes Exaggerated Behavioral Activation in Novel Environments

Abstract: The limbic system-associated membrane protein (LAMP) is a GPI-anchored cell adhesion molecule expressed heavily in limbic and limbic-associated regions of the developing and adult brain. Experimental studies show that LAMP promotes the growth of limbic neurons and guides the projections of limbic fibers. In order to examine the functional consequences of disrupting limbic circuit assembly, we generated a mouse line in which the Lsamp gene encoding LAMP was deleted. Basic neuroanatomical organization and sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 57 publications
(87 reference statements)
4
49
1
Order By: Relevance
“…First, the deletion in case 14, telomeric of the SRO, contains LSAMP and GAP43 , two strong candidate genes for developmental delay. LSAMP encodes the limbic system associated membrane protein, and studies in both human and mice models have demonstrated the involvement of LSAMP in neuropsychiatric features and behaviour 30 31. GAP43 is involved in neurite outgrowth, neurotransmission, and synaptic plasticity among other functions and GAP43 was also recently identified as a candidate gene for autism and autistic-like manifestations in human and mice 32–34.…”
Section: Resultsmentioning
confidence: 99%
“…First, the deletion in case 14, telomeric of the SRO, contains LSAMP and GAP43 , two strong candidate genes for developmental delay. LSAMP encodes the limbic system associated membrane protein, and studies in both human and mice models have demonstrated the involvement of LSAMP in neuropsychiatric features and behaviour 30 31. GAP43 is involved in neurite outgrowth, neurotransmission, and synaptic plasticity among other functions and GAP43 was also recently identified as a candidate gene for autism and autistic-like manifestations in human and mice 32–34.…”
Section: Resultsmentioning
confidence: 99%
“…Deletion of Nr-CAM in mice results in an altered behavioral phenotype reflective of increased impulsivity (Matzel, et al 2008). Deletion of the CAM Lsamp in mice leads to heightened reactivity to novelty (Catania, et al 2008) and conditional deletion of L1-CAM in brain results in decreased anxiety-like behavior (Law, et al 2003). Epilepsy and neuropsychiatric disease have a bidirectional relationship of comorbidity (Dixon-Salazar, et al 2004; Gargus 2006; Jacoby and Thapar 2009; Pauli and Stefan 2009; Spence and Schneider 2009) and thus may share common genetic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…This comes from a study using knockout mice for the limbic system-associated membrane protein (LSAMP). These mice showed increased novelty reactivity and impaired learning (Catania et al 2008, Qiu et al 2010, and associated with this, a reduction in non-genomic MR function in the hippocampus (Qiu et al 2010).…”
Section: Adaptation Of Behaviour and Cognitionmentioning
confidence: 96%